MAVS polymers smaller than 80 nm induce mitochondrial membrane remodeling and interferon signaling. (16th February 2019) - Hwang, Ming‐Shih; Boulanger, Jérôme; Howe, Jonathan D.; Albecka, Anna; Pasche, Mathias; Mureşan, Leila; Modis, Yorgo
Abstract : Double‐stranded RNA (dsRNA) is a potent proinflammatory signature of viral infection and is sensed primarily by RIG‐I‐like receptors (RLRs). Oligomerization of RLRs following binding to cytosolic dsRNA activates and nucleates self‐assembly of the mitochondrial antiviral‐signaling protein (MAVS). In the current signaling model, the caspase recruitment domains of MAVS form helical fibrils that self‐propagate like prions to promote signaling complex assembly. However, there is no conclusive evidence that MAVS forms fibrils in cells or with the transmembrane anchor present. We show here with super‐resolution light microscopy that MAVS activation by dsRNA induces mitochondrial membrane remodeling. Quantitative image analysis at imaging resolutions as high as 32 nm shows that in the cellular context, MAVS signaling complexes and the fibrils within them are smaller than 80 nm. The transmembrane domain of MAVS is required for its membrane remodeling, interferon signaling, and proapoptotic activities. We conclude that membrane tethering of MAVS restrains its polymerization and contributes to mitochondrial remodeling and apoptosis upon dsRNA sensing. Abstract : Recognition of viral RNA triggers a potent innate immune response by inducing self‐assembly of the mitochondrial antiviral‐signaling protein (MAVS) via its caspase recruitment domain into helical fibrils with prion‐like properties. Super‐resolution light microscopy shows that MAVS activation by double‐stranded RNA induces mitochondrial remodeling, and that MAVS signaling complexes are smaller than 80 nm. The MAVS transmembrane domain is required for its membrane remodeling, signaling, and proapoptotic activities.